2016
DOI: 10.1371/journal.pone.0156917
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Sensitivity of QuantiFERON-TB Gold In-Tube and T-SPOT.TB According to Patient Age

Abstract: Currently, there are two types of interferon-gamma release assays (IGRAs) in use for the detection of tuberculosis (TB) infection, the QuantiFERON-TB Gold In-Tube test (GFT-GIT) and T-SPOT.TB. Owing to contradictory reports regarding whether the results of these IGRAs are affected by the age of the patient, we aimed to determine if these two tests have age-related differences in sensitivity. We retrospectively reviewed the medical records of diagnosed TB patients who were tested using either QFT-GIT or T-SPOT.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 37 publications
3
36
2
Order By: Relevance
“…Furthermore, The QFT-GIT is based on the ELISA method, while T-SPOT.TB assay is based on the ELISPOT method. The sensitivity of QFT-GIT is strongly affected by immunosuppressed status with only a slight effect of antigenic load, whereas the sensitivity of T-SPOT.TB is strongly affected by the antigenic load with only a slight effect of immunosuppressed status 11 , 26 . The present study enrolledspecified patients with active TB with nonimmunosuppressed conditions, seems to reduce the differences between the blood tests might provide slightly different results in generalization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, The QFT-GIT is based on the ELISA method, while T-SPOT.TB assay is based on the ELISPOT method. The sensitivity of QFT-GIT is strongly affected by immunosuppressed status with only a slight effect of antigenic load, whereas the sensitivity of T-SPOT.TB is strongly affected by the antigenic load with only a slight effect of immunosuppressed status 11 , 26 . The present study enrolledspecified patients with active TB with nonimmunosuppressed conditions, seems to reduce the differences between the blood tests might provide slightly different results in generalization.…”
Section: Discussionmentioning
confidence: 99%
“…One disadvantage of interferon-γ assays is that they can yield ITRs. Previous studies found that ITRs were common (ranging from 0% to 20%) when using QFT-GIT assay 14 , 15 , 26 , 28 , 34 . However, the majority of them were associated with immunosuppression or old age.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the prevalence of LTBI in the Republic of Korea and the importance of screening for LTBI in immunocompromised patients, who have an increased risk of M. tuberculosis reactivation after therapeutic interventions, the diagnostic performance of the screening methods is paramount. The overall sensitivity of QFT-GIT for the diagnosis of active tuberculosis infection in the Republic of Korean population has been reported to be 80.2% by Bae et al (30). However, the sensitivity or specificity of IGRAs for predicting the development of active tuberculosis is rather limited due to the need for long-term follow-up in the absence of a new exposure episode.…”
Section: Qft-plus (Concn In Tb2 Minus Concn In Nil Tube)mentioning
confidence: 99%
“…More recently, several companies have developed blood tests known as interferon-gamma release assays (IGRAs) as an alternative to TST in screening for LTBI. 19 21 These assays employ the innate ability of T cells to release interferon gamma in response to exposure to specific antigens. QuantiFERON-TB Gold In-Tube (QFT-GIT) assay is an IGRA that uses ELISA to quantify interferon-gamma release in vitro when patient’s whole blood is exposed to a cocktail of 3 mycobacterial proteins (ESAT-6, CFP-10, and TB 7.7).…”
Section: Introductionmentioning
confidence: 99%